Institutional Communication in the Process of Digital Transformation at the San Gregorio University of Portoviejo - Gereda Carrillo, Julio César (2024)
Institutional communication plays a fundamental role in the digital transformation process of academic institutions. The objective of this work is to determine the role of institutional communication in the digital transformation process of the Universidad San Gregorio de Portoviejo (USGP), Ecuador. A descriptive study was carried out with a quantitative approach, supported by the bibliographic review, the application of two questionnaires and the evaluation of the digital maturity of the institution using two reference matrices. It is determined that, although the majority of teachers and students demonstrate high skill in the management of educational platforms and digital tools, the data also indicate that there is a group within the academic community that still does not feel comfortable with the process of digitization. It is necessary to make improvements in the institutional communication of the USGP to facilitate the digital transformation process in the institution.